Development of Satureja cuneifolia-loaded sodium alginate/polyethylene glycol scaffolds produced by 3D-printing technology as a diabetic wound dressing material - OKTAR, FAİK NÜZHET; AKSU, MEHMET BURAK; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN; TAŞKIN, TURGUT (ELSEVIER, 2020)
Acute wounds are a common health problem, with millions of people affected and decreased granulation tissue formation and vascularization, it is also a big challenge for wound care researchers to promote acute wound healing around the globe. This study aims to produce and characterize Satureja cuneifolia plant extract (SC) blended with sodium alginate (SA) /polyethylene glycol (PEG) scaffolds for the potential treatment of diabetic ulcer. SA/PEG scaffolds were prepared by adding different concentrations (1, 3, and 5 wt%) of PEG to 9 wt% SA. The morphological and chemical composition of the resulting 3D printed composite scaffolds was determined using scanning electron microscopy (SEM) and Fourier transforms infrared spectroscopy (FTIR), respectively. Mechanical and thermal properties, swelling, and degradation behaviours were also investigated. The release kinetics of SC were performed. The antimicrobial analysis was evaluated against Escherichia coli and Staphylococcus aureus strains. 3D printed scaffolds have shown an excellent antibacterial effect, especially against gram-positive bacteria due to the antibacterial SC extract they contain. Furthermore, the cell viability of fibroblast (L929) cells on/within scaffolds were determined by the colourimetric MTT assay. The SA/PEG/SC scaffolds show a great promising potential candidate for diabetic wound healing and against bacterial infections. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Tissue engineering scaffolds; 3D printing; Diabetic wound healing; Satureja cuneifolia; ESSENTIAL OILS; IN-VITRO; ALGINATE; FIBROBLASTS; DEGRADATION; DELIVERY; CELLS; MODEL